Optimation Ca-Alginate Beads as Drug Reservoir in the Patch System for Model Anti-Inflammatory Drug - Hendradi, Esti; Isnaeni, Isnaeni; Mahmudah, Rifaatul (Health Notions, 2018)
The aim of this study was to optimize the use of Ca-Alginates beads as a drug reservoir in the patch system with and without freeze-drying process. Meloxicam, an anti-inflammatory non-steroidal drug, was used as a drug model. Ca-alginate beads were prepared by ionic gelation method using polymer alginate and cross-linker CaCl2. The beads were evaluated for its melting temperature, FTIR spectra, and entrapment efficiency. The FTIR study showed the loss of guluronic peaks of alginate caused by a cross-linking process with Ca2+, characteristics peaks of meloxicam still appeared indicating the compatibility of the drug with the polymers used. The using Ca-alginate beads without freeze-drying process as a drug reservoir resulted in a very wet patch that was difficult to dry, cracked surface, and pharmaceutically not acceptable. Meanwhile, patch using Ca-alginate beads with the freeze-drying process as a drug reservoir demonstrated satisfactory characteristics with minimum weight variation among the patches that lead to giving uniformity in the drug content.